Establishment and Characterization of Immortalized Minipig Neural Stem Cell Line. Issue 2 (February 2017) - Choi, Sung S.; Yoon, Seung-Bin; Lee, Sang-Rae; Kim, Sun-Uk; Cha, Young Joo; Lee, Daniel; Kim, Seung U.; Chang, Kyu-Tae; Lee, Hong J.
Despite the increasing importance of minipigs in biomedical research, there has been relatively little research concerning minipig-derived adult stem cells as a promising research tool that could be used to develop stem cell-based therapies. We first generated immortalized neural stem cells (iNSCs) from primary minipig olfactory bulb cells (pmpOBCs) and defined the characteristics of the cell line. Primary neural cells were prepared from minipig neonate olfactory bulbs and immortalized by infection with retrovirus carrying the v-myc gene. The minipig iNSCs (mpiNSCs) had normal karyotypes and expressed NSC-specific markers, including nestin, vimentin, Musashi1, and SOX2, suggesting a similarity to human NSCs. On the basis of the global gene expression profiles from the microarray analysis, neurogenesis-associated transcript levels were predominantly altered in mpiNSCs compared with pmpOBCs. These findings increase our understanding of minipig stem cells and contribute to the utility of mpiNSCs as resources for immortalized stem cell experiments.